Exploring synergistic and antagonistic interactions in phage-antibiotic combinations against ESKAPE pathogens - Kunz Coyne, Ashlan J.; Eshaya, Mirna; Bleick, Callan; Vader, Samantha; Biswas, Biswajit; Wilson, Melanie; Deschenes, Michael V.; Alexander, Jose; Lehman, Susan M.; Rybak, Michael J. (Microbiology spectrum, 2024)
In the face of escalating antimicrobial resistance, combining phages with antibiotics offers a promising avenue for treating infections unresponsive to traditional antibiotics. However, while studies have explored synergistic interactions, less attention has been given to potential antagonism and its impact on phage growth kinetics. This research evaluates the interplay between phages and antibiotics, revealing both synergistic and antagonistic patterns across various bacterial strains and shedding light on the complex dynamics that influence treatment efficacy. Understanding these interactions is crucial for optimizing combination therapies and advancing phage therapy as a viable solution for combating antimicrobial resistance.